Risk Factors of Breast Cancer - Anjar Nurrohmah; Anis Aprianti; Sri Hartutik (Gaster, 2022)
Background: Ca mamae is a cancer with the highest incidence and mortality of women in Indonesia and the world. Infodatin (2019) found that in the Dharmais Hospital in 2018 breast cancer occupied 19.18%. At Dr. Moewardi Hospital, it was shown that during 2018 Ca mamae had the highest incidence of cancer. Objective: to determine the risk factors for Ca mamae in Dr. Moewardi Hospital. Methods: This study is a descriptive with a cross sectional approach with checklist instrument. Sampling with purposive sampling with as many as 82 people as subjects. Results: The study showed that 75 (91.5%) of 82 people suffering from Ca mamae factor were 40 years old, 61 (74.4%) had a family history of suffering from Ca mamae, consuming alcohol as much as 43 (52.4%). ), were obese by 46 (56.1%), and experienced exposure to cigarette smoke as much as 65 (79.3%). Conclusion: Most of Ca mamae patients aged 40 years, have a family history of Ca mamae, consume alcohol, are obese and experience exposure to cigarette smoke. Suggestion: The importance of providing health education to women, so that they can find out the characteristics of Ca mamae patients so that prevention can be done.